Efforts to Stimulate Baby Growth and Development With Baby Massage Method - Ali, Sarina; Latuamury, Sitti R (Journal of Evidence-Based Community Health, 2024)
Early stimulation and balanced nutritional intake carried out at the age of 0–2 years is the right time to achieve optimal growth and development. Baby massage is a gentle massage that is very important for the growth and development of babies. Baby massage is an expression of love between parents and children through touching the skin which has a tremendous impact. Outreach activities regarding baby massage to increase the knowledge of midwives, mothers and the community regarding efforts to stimulate the growth and development of babies. The target of this PKM activity is to know and understand the positive impacts obtained in relation to efforts to stimulate the growth and development of babies using the baby massage method